Improving English Reading Comprehension Through Readable Applications in SMA Negeri 1 Purworejo - Jannah, Wardah Nuur; Dewi, Puspa; Johan, Andrian Nuriza (Department of English Language Education, Universitas Muhammadiyah Purworejo, Indonesia, 2024)
The Readable application is a digital platform to improve English language learning by providing simplified stories across various genres, supported by audio and word translation features. This research investigates the effectiveness of teaching reading comprehension through the Readable application and examines students' perceptions of its utility in learning. The study was conducted among eleventh-grade students at SMA Negeri 1 Purworejo during the 2024/2025 academic year, with a total sample of 72 students. A quasi-experimental design was used, with 36 students in the experimental (XI-I) and 36 in the control (XI-K) class. Findings showed a significant improvement in reading comprehension for the experimental group, with mean pre-test and post-test scores of 51.64 and 71.22, respectively. The two-tailed significance value was 0.00, below the 0.05 threshold, supporting the alternative hypothesis. Additionally, students provided positive feedback on the app, expressing that it made learning English more enjoyable and accessible. These results suggest that the Readable application is valuable for enhancing reading comprehension skills.